2021
DOI: 10.31557/apjcp.2021.22.3.971
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Concordance of Self- Versus Clinician- Sampling for HPV Testing among Rural South Indian Women

Abstract: Background: Despite being largely preventable, HPV-related cervical cancers continues to be the second highest cause of cancer deaths among Indian women. HPV testing using self-sampled samples may offer an opportunity to expand cervical cancer screening in India where there is currently a shortage of providers and facilities for cervical cancer screening. The study examines acceptability and concordance of self vs. clinician collected samples for HPVrelted cervical cancer screening among rural South Indian wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“… 10 , 11 , 23 - 27 , 29 - 37 , 39 - 47 , 49 , 50 , 54 , 57 - 60 , 63 - 65 , 68 - 71 , 74 Studies reported high satisfaction of self-collection among women, 10 , 11 , 30 , 36 , 42 , 43 , 50 , 58 , 62 , 63 , 65 , 68 , 70 that women were willing to perform self-collection again, 10 , 11 , 23 , 27 , 29 - 31 , 35 , 41 , 49 , 57 , 58 , 60 , 68 , 69 and to recommend self-collection to others. 10 , 11 , 27 , 29 , 30 , 32 , 49 , 50 , 68 Self-collection was commonly described as easy, 10 , 11 , 26 , 29 , 30 , 33 - 36 , 39 - 41 , 43 , 50 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 , 23 - 27 , 29 - 37 , 39 - 47 , 49 , 50 , 54 , 57 - 60 , 63 - 65 , 68 - 71 , 74 Studies reported high satisfaction of self-collection among women, 10 , 11 , 30 , 36 , 42 , 43 , 50 , 58 , 62 , 63 , 65 , 68 , 70 that women were willing to perform self-collection again, 10 , 11 , 23 , 27 , 29 - 31 , 35 , 41 , 49 , 57 , 58 , 60 , 68 , 69 and to recommend self-collection to others. 10 , 11 , 27 , 29 , 30 , 32 , 49 , 50 , 68 Self-collection was commonly described as easy, 10 , 11 , 26 , 29 , 30 , 33 - 36 , 39 - 41 , 43 , 50 ...…”
Section: Resultsmentioning
confidence: 99%
“… 68 Two studies compared practitioner-supported models with in-clinic collection versus mail-out or at-home collection models (n = 1 at-home testing, n = 1 opt-out); higher uptake was reported in mail-out/at-home testing models. 21 , 27 We note that in models that use a population-based mail-out approach, it is not always possible to confirm receipt of test, nor eligibility for screening (ie, hysterectomy). Thus, these lower-adoption measures may not accurately reflect participant engagement in programs.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous studies that have reported comparable performance of self-sampling to clinician collected samples. 16,17 To our knowledge, this is the first study that compares the performance between the self-collected and trained PHWs collected HPV samples. Our study also demonstrates comparable agreements between HPV-SS and HPV-PHW samples.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, resources are needed for one-to-one counseling for women before preparing them to undertake HPV-SS. 16 17 19 This strategy may not be feasible in human-resource-constrained countries like India. The art-based health promotion strategies have been proven effective in facilitating and mobilizing women among diverse settings.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, infections with Treponema pallidum, causing syphilisa disease that can affect the central nervous system and potentially lead to death in later stagesincreased from 6834 cases to 7889 between 2015 and 2019 [2,3]. In contrast, the incidence of infections with the human immunodeficiency virus (HIV) [4] has largely remained unchanged in Germany over the last 10 years, while it remains challenging in developing countries [2,5]. In 2019, the worldwide prevalence of HIV was about 38 million people [6], and Germany is one of the countries with the lowest HIV infection incidence in Europe, most likely due to its successful preventive work [7].…”
Section: Introductionmentioning
confidence: 99%